Generically intended, but specifically interpreted: when beauticians, musicians, and mechanics are all men. - Gygax P; Gabriel U; Sarrasin O; Oakhill J; Garnham A (Language & Cognitive Processes, 2008)
The influence of stereotype and grammatical information (masculine intended as generic) on the representation of gender in language was investigated using a sentence evaluation paradigm. The first sentence introduced a role name (e.g., The spies came out ...) and the second sentence contained explicit information about the gender of one or more of the characters (e.g., ...one of the women ...). The experiment was conducted in French, German, and English. In contrast to English, stereotypicality of role names had no influence on readers' male biased representations in French and German, where interpretations were dominated by the masculinity of the masculine (allegedly) intended as generic.